Variation in green density and moisture content of radiata pine trees in the Hume region of New South Wales - Chan, Julian Moreno; Walker, J. C.F; Raymond, C. A (Australian forestry, 2012)
SummaryVariation in green density and moisture content are relevant for log transport planning, weight-scaling systems, lumber drying and dynamic assessment of stiffness. The lack of published Australian reports on the subject prompted the present study (most studies with radiata pine have been carried out in New Zealand).Patterns of variation in green density and moisture content of radiata pine as influenced by age, site, thinning regime, height in the stem and season were investigated using paired stands of mature trees (34.5–36.5 y old) on contrasting sites and with various thinning regimes, and a stand of young trees (9 y old), in the Hume region of New South Wales. Destructive samples were taken from mature trees at successive heights in the stem, and from young trees at 1.3 m. The effect of extended drought was included by using data from separate studies. The effect of green density variation on weight scaling was determined by calculating weight-to-volume conversions for a number of stands under two climatic scenarios.Under normal climate, sapwood green density averaged about 1100 kg m⁻³ and showed little variation across ages, seasons, sites, thinning regimes and height in the stem. Sapwood saturation showed small but consistent differences with age, season and height in the stem, but practically no differences with site and thinning regime. For mature trees, sapwood saturation ranged from 90% at the base of the tree to 92–94% higher up in the stem, whereas for young trees it averaged 96% at 1.3 m height.Heartwood green density varied greatly with height in the stem, but showed no consistent differences with site and thinning regime; it ranged from about 550 to 630 kg m⁻³ at 1.3 m height across mature stands. Heartwood saturation averaged about 7% at 1.3 m, decreased from the base of the tree to 10.5 m followed by an increase up the stem, was higher in the high-altitude site and decreased slightly from winter to summer.Whole-section green density was driven by the ratio of sapwood to heartwood that in turn was affected primarily by age and height in the stem, followed by site and to a lesser extent by thinning regime. Season exerted practically no effect on whole-section green density. Whole-section green density varied-considerably between mature stands, ranging from 943 to 1023 kg m⁻³ at 1.3 m height, 928 to 996 kg m⁻³ at 10.5 m, and 960 to 1016 kg m⁻³ at 16 m.Whole-section green density and thus weight-to-volume conversions were significantly affected by site, age and severe drought, but not by thinning regime nor season. Using a common conversion factor between contrasting sites would lead to errors of 3–5%). The errors in applying such a factor to unthinned stands under severe drought would be 10% (large trees), 12% (average trees) and 25% (suppressed trees). The errors for the 9–10.5-y-old trees under normal climate would be 8–10% and up to 5% under severe drought. If a separate conversion factor was set for young trees, conversions under severe drought would have an error of 9–13%. It is then advisable to determine variations in green density at site and age levels in large plantation areas with a range of growing conditions and age classes, as well as to monitor changes during extended droughts.